2018
DOI: 10.1155/2018/5250843
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Women with Obstetric Fistula following Corrective Surgery: A Qualitative Study in Benadir and Mudug Regions, Somalia

Abstract: Obstetric fistula is a severe maternal morbidity which can have devastating consequences for a woman's life and is generally associated with poor obstetric services leading to prolonged obstructed labour. The predisposing factors and consequences of obstetric fistula differ from country to country and from community to community. The World Health Organization estimated that more than 2 million women in sub-Saharan Africa, Asia, the Arab region, Latin America, and the Caribbean are living with the fistula, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…In this study, VVF will be used as being synonymous with obstetric fistula. VVF may cause sufferers to experience chronic urinary/faecal incontinence, the stigma of continuing foul odour, social exclusion, and decreased quality of life [3][4][5]. VVF is primarily caused by prolonged obstructed labour, for which there are several known contributing factors such as giving birth at home in the absence of a midwife or skilled birth attendant can increase the likelihood of VVF [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, VVF will be used as being synonymous with obstetric fistula. VVF may cause sufferers to experience chronic urinary/faecal incontinence, the stigma of continuing foul odour, social exclusion, and decreased quality of life [3][4][5]. VVF is primarily caused by prolonged obstructed labour, for which there are several known contributing factors such as giving birth at home in the absence of a midwife or skilled birth attendant can increase the likelihood of VVF [6].…”
Section: Introductionmentioning
confidence: 99%
“…A dominant narrative is that stigmatised, incontinent women are abandoned by their husbands. Often, support for this narrative comes from interviews with women themselves7 16 and from international organisations conveying the gravity of fistula following childbirth 17. In contrast, a 2007 meta-analysis found that 36% (95% CI 27% to 46%) of women with fistula were divorced or separated, with substantial heterogeneity across geographies and authors 8.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that infants born to women with obstetric complications are 3.7 times more likely to die than those without complications (11). Economically, women spend 11% more than men in similar age groups on reproductive age morbidity treatment expenditures, 24% have di culty in resuming household work (12), and socially, some women are neglected by their husbands due to reproductive age morbidities such as stula, (13). The high levels of intimate partner violence among pregnant women may also exacerbate maternal morbidities (14).…”
Section: Introductionmentioning
confidence: 99%